MEASUREMENTS OF HOT CARRIER RELAXATION AND RECOMBINATION IN GaAs QUANTUM WELLS BY PICOSECOND OPTICAL PROBING. - Ryan, J; Taylor, R; Turberfield, A (IEE, 1984)
In this paper the authors show how picosecond time-resolved photoluminescence can be used to probe the energy relaxation of hot carriers in semiconductor structures. In addition, by measuring the variation of luminescence lifetime with carrier density one can obtain information about radiative and nonradiative decay processes. These processes are important in all photonic devices, but especially so in structures where interfaces may have a particularly strong influence.